Fallen Leaders dan Mereduksi Celebrity Pastor Culture dalam Perspektif Etis Teologi - Astria Gempita Fau; Yonathan Salmon Efrayim Ngesthi (Sekolah Tinggi Teologi Kanaan Nusantara, 2025)
The crisis of spiritual leadership marked by the moral downfall of church leaders (fallen leaders) poses a serious challenge to the spiritual integrity of the church today. This phenomenon does not stand alone but often stems from a culture of celebrity worship within church ministry that prioritises popularity over holiness. The culture of celebrity pastors has shifted the focus of ministry from Christ to the leader themselves, leading to abuse of authority, spiritual narcissism, and manipulation of the congregation. This phenomenon indicates a paradigm shift in leadership that no longer is based on Christian ethics and the spirituality of the cross. The purpose of this study is to critically examine how theological ethical perspectives can respond to and reduce the culture of celebrity in church leadership. Using a qualitative method with a literature review approach, it can be concluded that Christ-centred Leadership Theology is the antithesis of the culture of popularity that dominates current church leadership models. In this context, the culture of celebrity pastors creates an identity crisis for church leaders that can only be addressed through theological ethics and the integrity of theological education that reshapes leadership rooted in the spirituality of the cross.AbstrakKrisis kepemimpinan rohani yang ditandai oleh kejatuhan moral para pemimpin gereja (fallen leaders) merupakan tantangan serius bagi integritas spiritual gereja masa kini. Fenomena ini tidak berdiri sendiri, tetapi sering kali berakar pada budaya selebritisasi dalam pelayanan gereja yang mengagungkan popularitas lebih dari kekudusan. Budaya celebrity pastor telah menggeser orientasi pelayanan dari Kristus kepada diri pemimpin itu sendiri, yang berujung pada penyalahgunaan otoritas, narsisme spiritual, dan manipulasi jemaat. Fenomena ini mengindikasikan adanya pergeseran paradigma kepemimpinan yang tidak lagi berbasis pada etika Kristiani dan spiritualitas salib. Tujuan dari penelitian ini adalah untuk mengkaji secara kritis bagaimana perspektif etis teologi dapat merespons dan mereduksi budaya selebritisasi dalam kepemimpinan gereja. Menggunakan metode kualitatif dengan pendekatan studi pustaka maka dapat disimpulkan bahwa Teologi Kepemimpinan Kristus merupakan antitesis terhadap budaya popularitas yang mendominasi model kepemimpinan gereja masa kini. Dalam konteks ini, budaya pastor selebriti menciptakan krisis identitas pemimpin gereja yang hanya dapat dijawab melalui etika teologis dan integritas pendidikan teologi yang membentuk ulang kepemimpinan yang berakar pada spiritualitas salib.